At the Edge · In the Frame - Marlon Blackwell (Oz, 2000)
A truly felt work of architecture is that which has been freed from dualities. Within the multitude of forces inherent in a particular condition of place it is not a question of revealing paradoxical opposites, but of directing ordering forces to cohere, to build and store energy through their interactions. Ed. note: Two buildings by Marlon Blackwell, the Moore House and the Honey House. Text also by Blackwell.